Investigation of hybrid energy storage system with dynamic power and energy management for DC microgrid - Li, Tingting (2016)
Along with the development of many new technology, the demand of electrical energy is sharply growing, which engages better performance on Electrical Energy Storage. However, current ESS can not perfectly fulfill all requirements for different levels. Each single ESS has some shortages in certain aspect. In this case, a storage system which can take advantages from different single EESs and complement each other. That is Hybrid Energy Storage System. In this project, hybrid of Lead-acid battery and supercapacitor is studied. As one of the most widely used and oldest ESS at present, Lead-Acid battery has strong storage capacity and relatively low self-discharge rate but limited life cycle and low power density. In contrast, supercapacitor as a relatively new storage technology has high power density and large cycle efficiency but low energy density and high self-discharge rate. As a result, the integration of battery and supercapacitor should be of high energy density and high power density as well. This project will only discuss the MATLAB simulation of hybrid of battery and supercapacitor. Lead-acid battery and supercapacitor are connected to an DC/DC converter respectively before integrate them together. That can achieve the stable output of system and individual control for each subcomponent as well.